2014
DOI: 10.1007/s10930-014-9570-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Aspects of cAMP Dependent Protein Kinase Catalytic Subunit Allostery

Abstract: Kinetics of thermal inactivation of acrylodan-labeled cAMP dependent protein kinase catalytic subunit, its binary complexes with ATP and peptide inhibitor PKI[5-24], respectively, and the ternary complex involving both of these ligands were studied at different temperatures (5-50 °C). The thermodynamic parameters ΔH and ΔS for ligand binding equilibria as well as for the allosteric interaction between the binding sites of these ligands were obtained by using the Van't Hoff analysis. The results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Although it has been known that PKA-C exhibits K-type allosteric cooperativity (Kivi et al, 2014; Masterson et al, 2008), this work illuminates the structural basis for this phenomenon. The correlation we found between the conformational state of the ternary complex and the free energy of binding for the pseudo-substrate has many implications for kinase substrate recognition and function.…”
Section: Discussionmentioning
confidence: 83%
“…Although it has been known that PKA-C exhibits K-type allosteric cooperativity (Kivi et al, 2014; Masterson et al, 2008), this work illuminates the structural basis for this phenomenon. The correlation we found between the conformational state of the ternary complex and the free energy of binding for the pseudo-substrate has many implications for kinase substrate recognition and function.…”
Section: Discussionmentioning
confidence: 83%
“…This conclusion was previously confirmed by the results of computational analysis of PKAc specificity against short peptide substrates (MenaUlecia et al 2014), listing the interatomic interactions that are responsible for mo lec ular recognition of the peptide structure by the enzyme active center. Although the physical meaning of this con clusion is not very obvious because the entropy factor may play some role in PKAc interaction with peptides (Kivi et al 2014), it would not be surprising if the observed dif ferences in short peptide binding effectiveness were pre dominantly enthalpy driven. Certainly, this conclusion cannot be automatically extended to peptide binding with PKAc in general, and it would be interesting to perform a similar analysis in the case of the binding of long peptides.…”
Section: Docking Energy and Peptide Structurementioning
confidence: 91%
“…In this paper, the allosteric effect of ATP on the dock ing energy of a series of peptide substrates with PKAc was modeled computationally, and the results of these calcu lations were compared with the experimental data pre sented in our previous papers (Kuznetsov and Järv 2008;Kivi et al 2014). To overcome the limitations of con ventional docking algorithms, which do not consider alteration of the protein structure by ligand binding (Chen 2015), a timeeffective approach was proposed in which docking analysis was alternately combined with opti mization of the protein structure by molecular dynamics calculations.…”
mentioning
confidence: 99%